Stochastic integer programming models for reducing wastages and shortages of blood products at hospitals - Gunpinar, Serkan; Centeno, Grisselle (Computers & operations research, 2015)
Major challenges in the management of the blood supply chain are related to the shortage and wastage of the blood products. Given the perishable characteristics of this product, storing an excessive number of blood units on inventory could result on the wastage of this limited resource. On the other hand, having shortages may result in cancellations of critical health related activities and as a result a potential increase on fatality rates at hospitals. This paper presents integer programming models to minimize the total cost, shortage and wastage levels of blood products at a hospital within a planning horizon. The primary focus is on the red blood cells and the platelet components of the whole blood cells. The stochastic and deterministic models included consider uncertain demand rates, demand for two types of patients, and crossmatch-to-transfusion ratio. Results show wastage rates decreasing from 19.9% to 2.57% on average. In addition, the shortages and total cost are reduced 91.43% and 20.7% respectively for a given capacity increases. Computational results are included and discussed.